2017
DOI: 10.19109/jpmrafa.v3i1.1444
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pembelajaran Materi Perbandingan Menggunakan Konteks Resep Empek-Empek Untuk Medukung Kemampuan Bernalar Siswa SMP

Abstract: Bernalar dalam perbandingan merupakan salah satu topik penting pada pembelajaran matematika SMP. Penelitian ini bertujuan menghasilkan lintasan belajar materi perbandingan menggunakan konteks resep empek-empek dan bagaimana konteks tersebut dapat mendukung kemampuan bernalar siswa. Pendekatan pembelajaran yang digunakan adalah Pendidikan Matematika Realistik Indonesia (PMRI). Subjek penelitian adalah 45 siswa kelas VII SMPN 55 Palembang. Metode penelitian yang digunakan adalah design research, dugaan lintasan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Some research indicates that PMRI can improve the students in solving the problems of comparison (Sudarman, 2006); having influences which tend to be large against students memory on the sub-material ratio (Atiqa and Kusrini, 2000); improving students' communication capabilities on the subject of comparison (Askin and Junaedi, 2013); helping students to solve comparison problems with the students strategies and analogy themselves (Ning, 2016); supporting students' reasoning ability (Utari, 2015); and improvig students' understanding of learning about same value comparison (Rahmawati, 2015).…”
Section: Pmri Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research indicates that PMRI can improve the students in solving the problems of comparison (Sudarman, 2006); having influences which tend to be large against students memory on the sub-material ratio (Atiqa and Kusrini, 2000); improving students' communication capabilities on the subject of comparison (Askin and Junaedi, 2013); helping students to solve comparison problems with the students strategies and analogy themselves (Ning, 2016); supporting students' reasoning ability (Utari, 2015); and improvig students' understanding of learning about same value comparison (Rahmawati, 2015).…”
Section: Pmri Approachmentioning
confidence: 99%
“…An Australian study showed that students had difficulty in applying the ratio and proportion (Livy & Vale, 2011). Recent studies in Palembang Indonesia, as research conducted by Rahmawati (2015), Utari (2015), and Ningsih (2016) also shows there are still student difficulties in understanding the concept of comparison. Students' difficulties to understand the concept of comparison due to several factors, including ability in proportional reasoning is low.…”
mentioning
confidence: 99%
“…Learning in the PMRI approach starts from real events that have been experienced by students (Mubharokh et al, 2022). The use of contextual problems makes students more familiar with the problems given, so that it can help students learn to identify comparisons in everyday life (Utari, 2017). One of the typical cultural contexts of Palembang is Palembang jumputan fabric which has its own characteristics and peculiarities both in terms of color and motif (Dewi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PISA problems also use a global context that is not close to the daily lives of students in Indonesia. As a result, Indonesian students cannot imagine the relevance of the problems to their mathematics understanding, because the use of local cultural contexts, such as Jambi (Charmila et al, 2016;Muslimahayati, 2019), Lampung (Putra et al, 2016), Palembang (Utari, 2017), North Sumatra (Hasanah, 2017), can help students understand the mathematical content contained in the problems. Therefore, to familiarize Indonesian students' interest and accustom to solve mathematical problems in the form of reasoning and problem solving, it is necessary to apply innovation in developing PISA-like mathematical problems with contexts that are close to student life.…”
Section: Introductionmentioning
confidence: 99%